A record of the main speeches given by the Provost of Trinity College Dublin, Dr Patrick J Prendergast Academic Year 2012 - 2013 - Prendergast, Patrick J. (Trinity College Dublin, The University of Dublin, 2013)
A record of the main speeches given by the Provost of Trinity College Dublin, Dr Patrick J Prendergast Academic Year 2012 - 2013
Keywords: Speeches